Pengaruh Model Game Based Learning Terhadap Aktivitas Belajar Siswa Pada Pembelajaran Matematika di Kelas V SD Muhammdiyah 01 Medan - Siregar, Pebri Dayani; Sitepu, Melyani Sari (Journal of Student Development Informatics Management (JoSDIM), 2023)
The Influence Of The Game Based Learning Model On Student Learning Activities In Learning MathematicsÂ  Class V SD Muhammadiyah 01 Medan. The purpose of this study was to determine the effect of the Game Based Learning model on student learning activities in mathematics learning in class V SD MUhammdiyah 01 Medan. This research was conducted at SD Muhammadiyah 01 Medan, which is located at Jl. Demak No 3, Sei Renggas Permata, Kec. Medan Area, Medan city, North Sumatra 20211. The population in this study were all fifth grade students, totaling 42 people. The research instrument used an observation sheet totaling 19 valid statement items. The data analysis method used is the expert validity test, normality test, homogeneity test, and hypothesis testing ( t-test) using spss 26 software. The highest score was obtained 66 and lowest score was obtained 54 with an average score of 58.09 in the good category, while the learning activities of students in the control class of 20 students obtained a total score of 880, while highest score was obtained 58 and the lowest value was obtained 32 with an average score 44 categories is good enough. The results of testing the hypothsis on the output can be seen in the sig value. (2-tailed) is 0.000 < 0.05. Based on the analysis of the data obtained, the conclusion from the results of this study is tha there is an influence of the Game Based Learning model on student learning activities in mathematics learning in class V SD Muhammdiyah 01 Medan.